Figure 3 from: Cao S, Zhang F, Zheng H, Liu C, Peng F, Zhou Q (2018) Coccomyxa antarctica sp. nov. from the Antarctic lichen Usnea aurantiacoatra. PhytoKeys 98: 107-115. https://doi.org/10.3897/phytokeys.98.25360 - Cao, Shunan; Zhang, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Peng, Fang; Zhou, Qiming (Zenodo, 2018)
Figure 3 The NJ tree based on ITS rDNA (a) and SSU rDNA (b) sequences phylogenetic analyses. The sequences obtained by the authors were exhibited in bold font. The clades referred to Malavasi et al. (2016).